Cultivating power: Gardens in the global politics of diplomacy, war, and peace - CALLAHAN, William A. (Institutional Knowledge at Singapore Management University, 2017)
Although gardens are typically appreciated as peaceful spaces of apolitical serenity, this article highlights how gardens can provide new sites and sensibilities that complicate our understanding of diplomacy, war, and peace. While gardens are a popular location for diplomatic performances—for example, the Treaty of Versailles—the global politics of gardens remains underresearched in international relations (IR). To address this gap, the article follows the “aesthetic turn” in IR to examine gardens as contingent social constructions of social-ordering and world-ordering, which both shape and participate in global politics. In particular, it develops a framework to examine how peace-war becomes intelligible in gardens through contingent conceptual dynamics such as “civility/martiality.” It then employs the framework to explore how two key national memorial sites—the Nanjing Massacre Memorial in China and the Yasukuni Shrine in Japan—work as gardens to creatively perform civility and martiality in unexpected ways. Such an oblique intervention underlines how war memorials, gardens, and other odd IR sites are not stable containers of meaning but need to be actively (re)interpreted as performances of cultural governance and resistance. Garden-building here is theory-building: by producing new sites and sensibilities of global politics, it creatively shapes our understanding of IR.